THE URGENCY OF EVALUATION OF EDUCATION AND LEARNING A THEORETICAL REVIEW - Ujang Miftahudin; Nova Sariwati; Mohamad Erihadiana; Zam zam Lukmanul Jamil (LP2M IAIN Sultan Amai Gorontalo, 2025)
Evaluation of education and learning is a crucial element in the educational process that aims to ensure the achievement of predetermined educational goals. Evaluation not only serves to measure learners' learning outcomes but also to identify strengths and weaknesses in the learning process and provide constructive feedback for continuous improvement. In this theoretical review, the author will review various perspectives and theories related to the importance of evaluation in education and learning. The review covers the definition, purpose, and types of evaluation, as well as methods and techniques that can be used to conduct effective evaluation. It also highlights the challenges and solutions in the implementation of educational evaluation across different levels and contexts of education. Through a comprehensive understanding of the urgency of evaluation, it is hoped that educators and policymakers can design and implement more effective evaluation strategies to improve the overall quality of education.